Loom weights as a research tool - Boertien, Jeannette (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
The function of loom weights was to stretch and space the warp threads on a vertical loom. The loom weight is often the only preserved remnant of a loom used in antiquity. Because of their ubiquity, loom weights are the main key to the study of textile production in the Iron Age in the Levant. During excavations loom weights are easy to recognize if they are made of metal, stone or ceramics. Within burnt layers, unfired clay loom weights can be accidentally fired and thus well preserved. But it is difficult to recognize and securely excavate unfired raw clay loom weights. The two main problems are: 1. Unfired loom weights disintegrate when they get wet. 2. When excavating a mudbrick site, the clay of the loom weights resembles the matrix they were found in. Clay loom weights were sometimes fired, resulting in durable terracotta weights, but the majority were made of unfired clay. Unlike Staermose Nielsen (Staermose Nielsen, K.-H. In: Pritchard, F. and J.F. Wild (ed.). Northern Archaeological Textiles NESAT VII. Oxbow Books, Oxford, 2005:130), who states: “Groups of unbaked clay weights are the more numerous of all, but as clay loom weights reveal themselves on excavations only as disintegrated lumps, their usefulness in a classification is minimal.” For many excavations Staermose Nielsen is right. But that is because of the way the weights are excavated rather than preserved in the ground. I will demonstrate that clay loom weights, when properly excavated and preserved, can be classified and studied in a meaningful way, enabling us to reconstruct textile production. The practical part. I would like to share a registration form for loom weights to be used in excavations and research projects (see abstract link below). Your comments and ideas on my conceptual form are very welcome!